2012
DOI: 10.3390/s120911571
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between Weather Variables and Electric Power Demand inside a Smart Grid/Smart World Framework

Abstract: One of the main challenges of today's society is the need to fulfill at the same time the two sides of the dichotomy between the growing energy demand and the need to look after the environment. Smart Grids are one of the answers: intelligent energy grids which retrieve data about the environment through extensive sensor networks and react accordingly to optimize resource consumption. In order to do this, the Smart Grids need to understand the existing relationship between energy demand and a set of relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 35 publications
2
55
0
3
Order By: Relevance
“…This makes sense, as seasons are roughly outlined, together with summer holidays (August) and Christmas (December). Electricity demand is seasonally dependent, as shown by Hernández et al [27]. 3.…”
Section: Classification With Self-organizing Mapmentioning
confidence: 97%
“…This makes sense, as seasons are roughly outlined, together with summer holidays (August) and Christmas (December). Electricity demand is seasonally dependent, as shown by Hernández et al [27]. 3.…”
Section: Classification With Self-organizing Mapmentioning
confidence: 97%
“…ANNs and WNNs include weather information, as it was shown that weather has a considerable Chapter 4. Implementation influence upon the energy consumption (Hernndez et al, 2012). The statistical methods rely on time-series regression in order to generate the prediction, and thus only use historical demand records.…”
Section: Fig 44: Variables Correlationmentioning
confidence: 99%
“…It has been designed and implemented using the INGENIAS MAS methodology [14]. System agents are represented through roles which are reusable pieces of functionality.…”
Section: A Mas Oriented Framework For Vpp Controlmentioning
confidence: 99%